'A cross burning darkly, blackening the night': Reading racialized spectacles of conflict and bondage in Marvel's early Black Panther comics. Issue 1 (1st June 2018) - Peppard, Anna F.
All superheroes embody cultural messages and negotiate cultural conflicts. Yet black bodies, introduced to the New World as property and rigorously and often violently regulated by interconnected cultural and institutional forces ever since, have always occupied an especially vexed place in American culture. While all superheroes face repeated threats to their physical integrity, America's first black superhero, Marvel's Black Panther, created in 1966 by Stan Lee and Jack Kirby, faces the specific – and specifically risky – challenge of performing black embodiment without succumbing to the stereotypes of black embodiment, most notably the stereotype of black bodies being more bodily (re: more violent, more sexual, more animalistic) than white bodies. This article argues that although Black Panther's early appearances in The Fantastic Four (1961–present), The Avengers (1963–present) and his first solo series, Jungle Action Featuring: The Black Panther (McGregor et al. 1973–76) exploit the superhero genre and comic book medium's propensity for fantasy and iconic imagery to envision a blackness that is beautiful and liberating, depictions of Black Panther's conflicts with racialized supervillains and animals as well as his routine depiction within gratuitous spectacles of suffering and bondage demonstrate a simultaneous – and occasionally overwhelming – tendency to appropriate the black body in the service of white desires and anxieties. Ultimately, this article asserts that Black Panther's early stories prove both the power of comic book images and the danger of that power for subjects who are still fighting an uphill to be seen without being reduced to their visibility.